Metabolomic Analysis of Aqueous Humor Identifies Aberrant Amino Acid and Fatty Acid Metabolism in Vogt-Koyanagi-Harada and Behcet’s Disease - Xu, Jing; Su, Guannan; Huang, Xinyue; Chang, Rui; Chen, Zhijun; Ye, Zi; Cao, Qingfeng; Kijlstra, Aize; Yang, Peizeng (Frontiers in Immunology, 2021)
To investigate aqueous metabolic profiles in Vogt-Koyanagi-Harada (VKH) and Behcet’s disease (BD), we applied ultra-high-performance liquid chromatography equipped with quadrupole time-of flight mass spectrometry in aqueous humor samples collected from these patients and controls. Metabolite levels in these three groups were analyzed by univariate logistic regression. The differential metabolites were subjected to subsequent pathway analysis by MetaboAnalyst. The results showed that both partial-least squares discrimination analysis and hierarchical clustering analysis showed specific aqueous metabolite profiles when comparing VKH, BD and controls. There were 28 differential metabolites in VKH compared to controls and 29 metabolites differential metabolites in BD compared to controls. Amino acids and fatty acids were the two most abundant categories of differential metabolites. Furthermore, pathway enrichment analysis identified several perturbed pathways, including pantothenate and CoA biosynthesis when comparing VKH with the control group, and D-arginine and D-ornithine metabolism and phenylalanine metabolism when comparing BD with the control group. Aminoacyl-tRNA biosynthesis was altered in both VKH and BD when compared to controls. Our findings suggest that amino acids metabolism as well as two fatty acids, palmitic acid and oleic acid, may be involved in the pathogenesis of BD and VKH.